Determination of moment of inertia for 162-168Hf and 164-176Yb deformed nuclei - Okhunov, Abdurahim; Abu Kassim, Hasan; Usmanov, Phazlitdin (Penerbit UKM, 2011)
In this paper, a method of defining the even-even deformed nuclei inertial parameters is suggested. Calculations for isotopes 162-168 Hf and 164-176 Yb are listed. The parameters of inertia of rotational nuclei are also defined. Dependence of the parameters of inertia on the nucleons number is shown.